An Analysis of the Poetry of Azzedine Mihoubi and Ahmad Shāmlū Based on Pierre Guiraud’s Theory of Social Semiotic - Atefeh Rahmani; Mahin Hajizadeh; Abdolahad Gheibi (مطالعات زبانی و بلاغی)
Pierre Guiraud’s theory of social semiotics is part of his study on semiotics in which he categorizes signs into logical, aesthetic, and social. In this approach, signs are deemed by humans to be social phenomena with functions, contexts and impacts. Signs are concerned with the social meaning that is present in texts and human societies. For a social semiologist, text is the background against which the meaning produced by social forces emerges. Using the comparative-analytic method based on the American School, this study has applied social semiotics to Azzedine Mihoubi and Ahmad Shāmlū’s poetry. The research results show that social semiotics in both poets’ works is manifested as codes of identity, tone, expletives, rituals and ceremonies, fashion and game. These codes have turned, in the form of shared themes and topics, into symbols as they enter the space of poetic experience and constitute a particular collection. Such collections, examined in the light of social codes, are among the similarities between the works of the two poets. By using each code, the concealed layers and poetic concepts can be grasped. However, the type of poetic (personal and social) feelings and cultural and religious differences are among the dissimilarities between the two poets’ work.